Pemodelan Tingkat Kerawanan Pangan Rumah Tangga di Indonesia Tahun 2021 dengan Pendekatan Regresi Logistik Ordinal - Aguilera, Tasya; Jatmiko, Yogo Aryo (Indonesian Journal of Applied Statistics, 2022)
Until 2021, Indonesia has succeeded in reducing the prevalence rate of the population with moderate or severe food insecurity. But on the other hand, Indonesia's Global Food Security Index (GFSI) score which has declined in the last three years shows that Indonesia's food security is getting weaker in various aspects. The condition of food security that begins to weaken can trigger food insecurity. Food insecurity that can have an impact on health, nutrition and health system problems is a national health problem that needs attention. Therefore, this study aims to examine the level of household food insecurity and the variables that influence it. This study uses The National Socioeconomic Survey (Susenas) March 2021 data which was analyzed using partial proportional odds model (PPOM) ordinal logistics regression method. In general, the results show that variables area of residence, gender, age, education, business field, number of household members, residence ownership status, and per capita expenditure affect the level of household food insecurity in Indonesia in 2021.Keywords: food insecurity; ordinal logistic regression; PPOM